2014
DOI: 10.1007/s12098-013-1295-1
|View full text |Cite
|
Sign up to set email alerts
|

The Need of Pediatric Palliative Care Education Among Pediatric Postgraduates in South India

Abstract: There is a huge lacunae in the delivery of palliative care services and hence an urgent need to inculcate targeted curriculum to provide focused skills and training for the pediatric postgraduates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…In general, teams feel affected by parents' resistance to discussing prognosis or dealing with the possibility of losing the child, or when there are unrealistic expectations. 13,16,17…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In general, teams feel affected by parents' resistance to discussing prognosis or dealing with the possibility of losing the child, or when there are unrealistic expectations. 13,16,17…”
Section: Discussionmentioning
confidence: 99%
“…In general, teams feel affected by parents' resistance to discussing prognosis or dealing with the possibility of losing the child, or when there are unrealistic expectations. 13,16,17 Another obstacle was the lack of a CPP team. It is known that PC can be made available in different modalities: Hospital Advisory Teams, Hospital Units, Hospice, Home care and specialized outpatient clinics.…”
Section: Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Studies have shown that pediatric residents are often not provided with adequate education in palliative care, with many receiving no formal training. 2 Even within subspecialties such as pediatric hematology/oncology, where death and poor prognoses are more commonly encountered, the formal education in palliative care is limited. While considered to be important by training program directors, the majority of programs lack significant formal training, 3 and pediatric residents report inadequate training in multiple domains of palliative and end-of-life care.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing the educational needs of practicing health professionals is an important step to improve access to palliative care for children living in resource limited settings, however, there are very few health professional training programs in LMICs that have incorporated training about pain management or palliative care into their curricula (9). In a previous study of pediatric physicians in South India, 87% strongly believed that more training in pediatric palliative care was required in postgraduate training curricula (10).…”
mentioning
confidence: 99%